A stochastic dominance test under survey nonresponse with an application to comparing trust levels in Lebanese public institutions - Fakih, Ali (2020)
Stochastic dominance comparisons of distributions based on ordinal data arise in many areas of economics. This paper develops a testing procedure for such comparisons under survey sampling from large finite populations with nonresponse using the worst-case bounds of the distributions. The advantage of using these bounds in distributional comparisons is that conclusions are robust to the nature of the nonresponse-generating mechanism. While these bounds on the distributions are often too wide in practice, we show that they can be informative for distributional comparisons in an empirical analysis. This paper examines the dynamics of trust in Lebanese public institutions using the 2013 wave of the World Values Survey as well as the 2016 and 2018 waves of the Arab Barometer, and finds convincing evidence of a decrease in confidence in most public institutions between 2013 and 2016.